Case report: Complete and durable response to larotrectinib (TRK inhibitor) in an infant diagnosed with angiosarcoma harbouring a KHDRBS1-NTRK3 fusion gene - Cervi, Catherine; Sápi, Zoltán; Bedics, Gábor; Zajta, Erik; Hegyi, Lajos; Pápay, Judit; Dezső, Katalin; Varga, Edit; Mudra, Katalin; Bödör, Csaba; Csóka, Monika (Frontiers in Oncology, 2023)
Significant improvements in the survival rates of paediatric cancer have been achieved over the past decade owing to recent advances in therapeutic and diagnostic strategies. However, disease progression and relapse remain a major challenge for the clinical management of paediatric angiosarcoma. Comprehensive genomic profiling of these rare tumours using high-throughput sequencing technologies may improve patient stratification and identify actionable biomarkers for therapeutic intervention. Here, we describe the clinical, histopathological, immunohistochemical and molecular profile of a novel and precision medicine-informed case where a KHDRBS1-NTRK3 fusion determined by next-generation sequencing-based comprehensive genomic profiling led to complete and sustained remission (clinical and radiological response) in an otherwise incurable disease. Our patient represents the first paediatric angiosarcoma harbouring a targetable NTRK3 fusion in the literature and demonstrates the first example of targeting this alteration in angiosarcoma using larotrectinib, an NTRK inhibitor. Clinical and radiological remission was achieved in under two months of therapy, and the patient is currently in complete remission, 4 month after stopping larotrectinib therapy, which was given over 17 months with only mild side effects reported. Therefore, this remarkable case exemplifies the true essence of precision-based care by incorporating conventional pathology with the why, when, and how to test for rare oncogenic drivers and agnostic biomarkers in paediatric angiosarcoma.